Individual psychology and investment style. (2015) - Ackert, Lucy F.; Athanassakos, George; Church, Bryan K.
This paper sheds light on the individual characteristics associated with investment style. A vast literature documents the importance of individual personality in explaining variation in choice, yet many questions remain regarding the determinants of investment choices. We use an experimental method to isolate participants' preference for value vs. growth stocks. Recent research suggests that biology plays a significant role in determining investment style. We extend this research by examining whether measurable behavioural and personality factors predict investment style, including risk tolerance, time preference, overconfidence, personal evaluation of the investment opportunity, and character strengths. Importantly, we find that an individuals' personal affective assessment of an investment opportunity plays a significant role in the determination of investor style.